2015
DOI: 10.3389/fncel.2015.00342
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stress activates neurites and somata of myenteric neurons

Abstract: The particular location of myenteric neurons, sandwiched between the 2 muscle layers of the gut, implies that their somata and neurites undergo mechanical stress during gastrointestinal motility. Existence of mechanosensitive enteric neurons (MEN) is undoubted but many of their basic features remain to be studied. In this study, we used ultra-fast neuroimaging to record activity of primary cultured myenteric neurons of guinea pig and human intestine after von Frey hair evoked deformation of neurites and somata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 53 publications
(93 reference statements)
2
35
0
Order By: Relevance
“…Several studies have reported distinct mechanosensitive responses in enteric neurons to tensile stress (stretch), compressive stress (volume injection, glass probe, or von Frey hair), shear stress, and cell swelling (hypoosmotic solutions) (Dong, Jiang, Dong, & Mittal, 2014; Hibberd, Zagorodnyuk, Spencer, & Brookes, 2012; Kugler et al, 2015; Kunze et al, 1999; Kunze, Clerc, Furness, & Gola, 2000; Kunze et al, 1998; Mayer & Wood, 1975; Mazzuoli & Schemann, 2009, 2012; Spencer & Smith, 2004). While these studies suggest roles in mechanosen-sitivity sensing and control of muscle activity, as well as a servo-feedback loop (Mazzuoli-Weber & Schemann, 2015), the identities of the mechano-sensitive ion channels responsible for mechanotransduction are largely unknown.…”
Section: Mechanosensitive Ion Channelsmentioning
confidence: 99%
“…Several studies have reported distinct mechanosensitive responses in enteric neurons to tensile stress (stretch), compressive stress (volume injection, glass probe, or von Frey hair), shear stress, and cell swelling (hypoosmotic solutions) (Dong, Jiang, Dong, & Mittal, 2014; Hibberd, Zagorodnyuk, Spencer, & Brookes, 2012; Kugler et al, 2015; Kunze et al, 1999; Kunze, Clerc, Furness, & Gola, 2000; Kunze et al, 1998; Mayer & Wood, 1975; Mazzuoli & Schemann, 2009, 2012; Spencer & Smith, 2004). While these studies suggest roles in mechanosen-sitivity sensing and control of muscle activity, as well as a servo-feedback loop (Mazzuoli-Weber & Schemann, 2015), the identities of the mechano-sensitive ion channels responsible for mechanotransduction are largely unknown.…”
Section: Mechanosensitive Ion Channelsmentioning
confidence: 99%
“…It has been assumed that such disorders may arise from injury or death of mature enteric neurons in what has traditionally been thought to be a static system with little or no capacity for renewal 4 . The ENS is continually exposed to a variety of extrinsic factors such as diet, mechanical stretch, medications, and toxins with recent data suggesting that many of these can influence the structure and function of ENS 59 . The mechanism through which these extrinsic factors can affect ENS are not fully understood, but the gut microbiota is emerging as one of the main mediators of these effects.…”
Section: Introductionmentioning
confidence: 99%
“…13 Functionally, ENS neurons can be identified as motor neurons, intrinsic sensory or intrinsic primary afferent neurons, and interneurons, although different classes of interneurons are reported to have sensory functions, 15 while mechanosensitive neurites are shown to have afferent and efferent functions. 16 The ENS neurons code and use over 30 neurotransmitters/ mediators that are similar to those present in the central nervous system. 17 Cholinergic and nitrergic neurotransmissions are among the most abundant in the ENS and play key roles in the secretomotor, mucosal barrier, and immune responses of the human gut.…”
Section: The Enteric Nervous Systemmentioning
confidence: 99%